Respon Peserta Didik Terhadap Penggunaan Aplikasi Wordwall dalam Pembelajaran Bahasa Arab - Mohamad Rian Liputo; Endah Fazirah Hakim; Nur Ainiyah; Juliani A. Ma'atiala (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2023)
In this era, the integration of learning media such as Wordwall has become increasingly relevant. The use of technology in Arabic language learning is expected to stimulate students' interest, accelerate the comprehension process, and create a more dynamic learning environment. This study aims to determine how students respond to the use of the Wordwall application or media in Arabic language learning at the secondary school level. The research method used in this study is a descriptive quantitative approach, with the research location at MTs Negeri 1 Kota Gorontalo. The findings of this study indicate that the use of the Wordwall application in Arabic language learning at madrasas received a very positive response from students. By continuously implementing innovations like Wordwall, Arabic language learning in madrasas can continue to evolve and positively impact student development. This research highlights the importance of integrating technology into language education, particularly in enhancing student engagement and learning outcomes. The positive reception of Wordwall suggests that similar interactive digital tools could be beneficial in other language learning contexts. Further research could explore the long-term effects of such applications on language proficiency and retention.